2022
DOI: 10.4239/wjd.v13.i4.308
|View full text |Cite
|
Sign up to set email alerts
|

Gut microbiota and diabetic kidney diseases: Pathogenesis and therapeutic perspectives

Abstract: Diabetic kidney disease (DKD) is one of the major chronic complications of diabetes mellitus (DM), as well as a main cause of end-stage renal disease. Over the last few years, substantial research studies have revealed a contributory role of gut microbiota in the process of DM and DKD. Metabolites of gut microbiota like lipopolysaccharide, short-chain fatty acids, and trimethylamine N-oxide are key mediators of microbial–host crosstalk. However, the underlying mechanisms of how gut microbiota influences the on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 75 publications
0
19
0
Order By: Relevance
“…However, therapies based on these mechanisms have limited effects; more researches about DKD pathogenesis are essential and may provide new insights into treating DKD. Intriguingly, the gut microbiota as a novel intervention for diabetes and its complications, such as DKD, is now attracting more and more attention (4)(5)(6).…”
Section: Introductionmentioning
confidence: 99%
“…However, therapies based on these mechanisms have limited effects; more researches about DKD pathogenesis are essential and may provide new insights into treating DKD. Intriguingly, the gut microbiota as a novel intervention for diabetes and its complications, such as DKD, is now attracting more and more attention (4)(5)(6).…”
Section: Introductionmentioning
confidence: 99%
“…G_ Odoribacter , g_ ruminiclorstridium , g_ Adlercreutzia and G_ LachnospiraceaeNK4A136. The increase of this group and g_u_ruminococcaceae nk4a214 group accelerated the process of DKD ( 59 ). In prediabetes, or impaired glucose tolerance (IGT), researchers observed a significant decrease in Clostridium ( 60 ) and butyric-producing bacteria ( 39 ) in the intestinal flora, while there was an increase in Dolella .…”
Section: Discussionmentioning
confidence: 99%
“…Accumulating evidence has demonstrated that alterations of composition and function in gut microbiota were correlated with increased risk of the occurrence and development of diabetes and its associated complications (36). This review was designed to comprehensively characterize the alterations of gut microbiome in DKD, by comparing with diabetes, NDKD, and healthy controls.…”
Section: Discussionmentioning
confidence: 99%